Myocardial effects of hyperammonemia in a minimum hepatic encephalopathy animal model - Grimaldi, Santiago Fernando (2019)
Sarcopenia and heart failure are common features of chronic liver disease (CLD). The loss of skeletal muscle (SM) and its function contributes to morbidity and mortality. Its prevalence in patients with CLD is estimated at 40-70%. Hepatic encephalopathy\n(HE) has a similar prevalence and, in addition, there is a correlation between the two.\nThe CLD decreases the detoxification capacity of ammonia, so SM and astrocytes become the main route of ammonia, mainly through glutamine synthetase (GS). We\nhypothesized that a model of subclinical hepatic encephalopathy (MHE) showing moderate hyperammonemia and almost normal liver could show a starting point for\nearly events in myocardial (HM) damage. The Wistar rats were divided into 2 groups, (i) simulated surgery and (ii) group with stenosed portal vein, MHE. GS, oxygen consumption, nitric oxide production, light microscopy, high resolution light microscopy (HRLM) and electron transmission microscopy (ETM) were evaluated, after 14 days of surgery, in left HM. The results showed focal areas of fibrosis with Sirius red staining and a significant increase in GS (p <0.01) in the MHE group.\nHRLM showed that the HM triad (T-tubules and sarcoplasmic reticulum) was widely dilated with a convergent structure. This membrane traffic system was undulated with\nan increased surface, to the detriment of the fibrillar structure. ETM, confirmed these, showing subcellular edema, with detachment of fibrillar structures, swollen\nmitochondria with loss of ridges and matrix density, disruption of the nuclear\nmembrane and an increase in the number and size of subsarcolemal vacuoles. The triad was also altered showing the dilatation of this system and the focal interruption.\nThe most relevant ETM data were focal myofibrillolysis and wide alterations in\nmitochondria. These results suggest that under these conditions, in early stages of\nHE, hyperammonemia could induce myocardial cell damage, with or without CLD.